1986
DOI: 10.3758/bf03200043
|View full text |Cite
|
Sign up to set email alerts
|

A study of exploratory behavior as an index of spatial knowledge in hamsters

Abstract: This experiment investigated the role of exploration in the formation of maps of the environment. The effects of spatial rearrangement of four familiar objects in an open field on subsequent exploratory behavior were studied in hamsters (Mesocricetus auratus). During two exploratory sessions, four groups of subjects were exposed to objects in a particular spatial relation to each other and to a distal pattern. During a testing session, the control group was exposed to the same situation as during the first two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
1
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(105 citation statements)
references
References 19 publications
5
97
1
2
Order By: Relevance
“…Thus, whereas the fishes in the egocentric group only reached the new goal after visiting the unrewarded arm (formerly the rewarded arm), the fishes in the allocentric and ego-allocentric groups quickly learned to move toward the new goal by using the shortest trajectory. The reversal performances of the latter two groups reveal a capacity for rapidly detecting environmental changes (Poucet, Chapuis, Durup, & Thinus-Blanc, 1986;Thinus-Blanc et al, 1987;Welker & Welker, 1958). Warburton (1990) reported similar reversal learning differences in goldfish trained in an arena tank to find reward in either a directly or an indirectly cued location.…”
Section: Response To Reversal For Each Experimental Groupmentioning
confidence: 71%
“…Thus, whereas the fishes in the egocentric group only reached the new goal after visiting the unrewarded arm (formerly the rewarded arm), the fishes in the allocentric and ego-allocentric groups quickly learned to move toward the new goal by using the shortest trajectory. The reversal performances of the latter two groups reveal a capacity for rapidly detecting environmental changes (Poucet, Chapuis, Durup, & Thinus-Blanc, 1986;Thinus-Blanc et al, 1987;Welker & Welker, 1958). Warburton (1990) reported similar reversal learning differences in goldfish trained in an arena tank to find reward in either a directly or an indirectly cued location.…”
Section: Response To Reversal For Each Experimental Groupmentioning
confidence: 71%
“…When one object was moved outward, away from the square, the hamsters spent a significantly increased amount of time in contact with the object in the novel position; that is, they exhibited dishabituation. Poucet et al (1986) concluded from this finding that the hamsters were responding to changes in the shape of the array. However, the animals could also have been responding to the change in position of the single relocated object relative to the walls of the arena and/or to the stripe on the wall or to a change in the distance or angle between specific pairs or triads of objects.…”
mentioning
confidence: 89%
“…Hamsters (Poucet et al, 1986;Thinus-Blanc et al, 1987;Thinus-Blanc, Save, Poucet, & Buhot, 1991) and rats (Poucet, 1989;Poucet, Durup, & Thinus-Blanc, 1988) selectively reexplore one object when it is moved outward from a square array of objects. This is true regardless of whether the objects differ from each other (e.g., Thinus-Blanc et al, 1987, Experiment B) or are identical (Thinus-Blanc et al, 1987, Experiment G).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…to find food, mates and nests) within their environment. Until recently, however, the vast majority of research on navigation and spatial cognition has addressed the question of how animals return to rewarded locations in the horizontal plane, largely ignoring the vertical component ( [1][2][3][4][5][6] but see [7]). …”
Section: Introductionmentioning
confidence: 99%